Environmental impact aáeáment on a fictive soil conservation project, a minor field study in Nicaragua - Erlandáon, M.; Lindqvist, P. (Uppsala (Suecia), 2000)
Sumario (En)
Ilus.; 24 ref.
Keywords: IMPACTO AMBIENTAL; EVALUACION; CONSERVACION DE SUELOS; NICARAGUA